Bioaerosol biomonitoring: Sampling optimization for molecular microbial ecology. (20th April 2019) - Ferguson, Robert M. W.; Garcia‐Alcega, Sonia; Coulon, Frederic; Dumbrell, Alex J.; Whitby, Corinne; Colbeck, Ian
Abstract: Bioaerosols (or biogenic aerosols) have largely been overlooked by molecular ecologists. However, this is rapidly changing as bioaerosols play key roles in public health, environmental chemistry and the dispersal ecology of microbes. Due to the low environmental concentrations of bioaerosols, collecting sufficient biomass for molecular methods is challenging. Currently, no standardized methods for bioaerosol collection for molecular ecology research exist. Each study requires a process of optimization, which greatly slows the advance of bioaerosol science. Here, we evaluated air filtration and liquid impingement for bioaerosol sampling across a range of environmental conditions. We also investigated the effect of sampling matrices, sample concentration strategies and sampling duration on DNA yield. Air filtration using polycarbonate filters gave the highest recovery, but due to the faster sampling rates possible with impingement, we recommend this method for fine ‐scale temporal/spatial ecological studies. To prevent bias for the recovery of Gram‐positive bacteria, we found that the matrix for impingement should be phosphate‐buffered saline. The optimal method for bioaerosol concentration from the liquid matrix was centrifugation. However, we also present a method using syringe filters for rapid in‐field recovery of bioaerosols from impingement samples, without compromising microbial diversity for high ‐throughput sequencing approaches. Finally, we provide a resource that enables molecular ecologists to select the most appropriate sampling strategy for their specific research question.